2009
DOI: 10.1189/jlb.0109030
|View full text |Cite
|
Sign up to set email alerts
|

The membrane expression of Neisseria meningitidis adhesin A (NadA) increases the proimmune effects of MenB OMVs on human macrophages, compared with NadA– OMVs, without further stimulating their proinflammatory activity on circulating monocytes

Abstract: Hypervirulent MenB causing fatal human infections frequently display the oligomeric-coiled coil adhesin NadA, a 45-kDa intrinsic outer membrane protein implicated in binding to and invasion of respiratory epithelial cells. A recombinant soluble mutant lacking the 10-kDa COOH terminal membrane domain (NadA(Delta351-405)) also activates human monocytes/macrophages/DCs. As NadA is physiologically released during sepsis as part of OMVs, in this study, we tested the hypothesis that NadA(+) OMVs have an enhanced or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 21 publications
1
33
0
Order By: Relevance
“…Recent studies have shown that NadA is involved in interaction with and stimulation of immune cells during infection (2)(3)(4) and in binding to the human chaperone Hsp90 (5,6). Its predicted molecular structure is very similar to the known virulence-associated factors Yersinia adhesin A (YadA) and UspA2 (7,8), which suggests that NadA is a member of the OCA (oligomeric coiled-coil adhesin) family (9).…”
mentioning
confidence: 81%
“…Recent studies have shown that NadA is involved in interaction with and stimulation of immune cells during infection (2)(3)(4) and in binding to the human chaperone Hsp90 (5,6). Its predicted molecular structure is very similar to the known virulence-associated factors Yersinia adhesin A (YadA) and UspA2 (7,8), which suggests that NadA is a member of the OCA (oligomeric coiled-coil adhesin) family (9).…”
mentioning
confidence: 81%
“…Its adhesive role is important in the course of colonization of the human upper respiratory tract (10,35). Following the passage across the epithelium, meningococcus invades tissues and blood, where NadA can interact with human blood leukocytes and lead to enhanced immune stimulation (36)(37)(38)(39). For these reasons, NadA is to be considered an important meningococcal virulence factor, involved in progressively invasive steps of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Serum samples were analyzed with a suspension array system (Bio-Plex; Bio-Rad, Hercules, Calif., USA) for the quantification of 9 cytokines [IL-1α, -1β, -2, -4, -6 and -10, interferon-γ (IFN-γ) and TNF-α] following the manufacturer's instructions as previously described [14,15,17]. …”
Section: Methodsmentioning
confidence: 99%